2019
DOI: 10.1016/j.dental.2018.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to the role of interflavan linkages and galloylation of proanthocyanidins at sustaining long-term dentin biomodification

Abstract: Objectives: The interactivity of proanthocyanidins (PACs) with collagen modulates dentin matrix biomechanics and biostability. Herein, PAC extracts selected based on structural diversity were investigated to determine key PAC features driving sustained effects on dentin matrices over a period of 18 months. Methods: The chemical profiles of PAC-rich plant sources, Pinus massoniana (PM), Cinnamomum verum (CV), Hamamelis virginiana (HV) barks, and Vitis vinifera (VV) seeds, were obtained by diol UHPLC analysis af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 30 publications
0
45
0
4
Order By: Relevance
“…However, in subsequent studies, the monomeric nongalloylated counterpart (EGC) did not enhance the mechanical properties, thus limiting any further relationships. The present findings show that the phenolic -OH groups of the galloyl motif increase the compound's reactivity and hydrophilicity (Iglesias et al 2010;Vidal, Leme, et al 2014;Aydin et al 2019); however, the sustainability of the bioactivity was found to be diminished, which is plausible considering that the galloyl motif is prone to hydrolysis of the ester bond linkage (Lee et al 2010;Krook and Hagerman 2012).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…However, in subsequent studies, the monomeric nongalloylated counterpart (EGC) did not enhance the mechanical properties, thus limiting any further relationships. The present findings show that the phenolic -OH groups of the galloyl motif increase the compound's reactivity and hydrophilicity (Iglesias et al 2010;Vidal, Leme, et al 2014;Aydin et al 2019); however, the sustainability of the bioactivity was found to be diminished, which is plausible considering that the galloyl motif is prone to hydrolysis of the ester bond linkage (Lee et al 2010;Krook and Hagerman 2012).…”
Section: Discussionmentioning
confidence: 48%
“…Bioinspired approaches to address pitfalls associated with unstable dentin-resin interfaces target the reinforcement of the dentin ECM and dentin-resin adhesion through biomodification by plant-derived proanthocyanidins (PACs; Bedran-Russo et al 2008;Bedran-Russo et al 2012;Bedran-Russo et al 2014). Multiscale enhancement of the mechanical properties, biodegradability of dentin, and extended durability of dentinresin adhesive interfaces were reported for PAC extracts, specifically from Vitis vinifera (Vv) grape seeds (Leme et al 2015;Leme-Kraus et al 2017;Aydin et al 2019). Preliminary studies have indicated that the dentin biomodification potency is influenced by a rich structural diversity of PACs, such as the degree of polymerization (DP; Vidal, Leme, et al 2014), galloylation , and the stereochemistry or positioning of the hydroxyl groups (Dong et al 2013;Aydin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grape seed extract (GSE) contains proanthocyanidin (PA), a natural collagen cross-linker with polyphenolic compounds. Previous studies showed that plant-derived PAs are strong dentin biomodifying agents [ 9 ]. This agent was reported to strengthen collagen-based tissues by increasing collagen cross-links [ 10 ].…”
Section: Introductionmentioning
confidence: 99%